Some reflections on the understanding of the oxygen reduction reaction at Pt(111) - Gómez-Marín, Ana M.; Rizo, Ruben; Feliu, Juan M. (Beilstein Journal of Nanotechnology, 2013)
The oxygen reduction reaction (ORR) is a pivotal process in electrochemistry. Unfortunately, after decades of intensive research, a fundamental knowledge about its reaction mechanism is still lacking. In this paper, a global and critical view on the most important experimental and theoretical results regarding the ORR on Pt(111) and its vicinal surfaces, in both acidic and alkaline media, is taken. Phenomena such as the ORR surface structure sensitivity and the lack of a reduction current at high potentials are discussed in the light of the surface oxidation and disordering processes and the possible relevance of the hydrogen peroxide reduction and oxidation reactions in the ORR mechanism. The necessity to build precise and realistic reaction models, which are deducted from reliable experimental results that need to be carefully taken under strict working conditions is shown. Therefore, progress in the understanding of this important reaction on a molecular level, and the choice of the right approach for the design of the electrocatalysts for fuel-cell cathodes is only possible through a cooperative approach between theory and experiments.
Keywords: hydrogen peroxide oxidation; hydrogen peroxide reduction; oxygen reduction; Pt(111); stepped surfaces